Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979) - Wang, Chao; Gao, Yunyun; Pape, Thomas; Zhang, Dong (Zootaxa, 2019)
Sarcophaga Meigen, 1826 is proposed as a senior synonym of Cornexcisia Fan & Kano, 2000, syn. nov. and Fanzideia Xue, Verves & Du, 2011, syn. nov. Cornexcisia Fan & Kano, 2000, stat. rev. is given status as a subgenus and is considered a senior synonym of Fanzideia Xue, Verves & Du, 2011, syn. nov. at the subgeneric level. Cornexcisia is argued to contain S. (Cornexcisia) longicornuta (Fan & Kano, 2000), comb. nov., S. (C.) cygnocerca (Xue, Verves & Du, 2011), comb. nov., S. (C.) kurahashii (Shinonaga & Tumrasvin, 1979), subgen. comb. nov. (from Phallosphaera Rohdendorf) and S. (C.) suthep Pape & Bänziger, 2003, subgen. comb. nov. (from Rosellea Rohdendorf). Sarcophaga (C.) kurahashii is newly recorded from China (Yunnan), the male is redescribed and the female is described for the first time, supported by photographs, illustrations and mitochondrial cytochrome oxidase subunit I (COI) gene sequences. Species of Cornexcisia share an exceptionally long postpedicel in the female and the following apomorphic distiphallic appendages in the male: juxta ventro-proximally with an apically divided arm with cuticular pile, and lateral styli bifurcated from the base with each branch elongate, gently curved and slightly expanded apically. A key to the species of Cornexcisia is provided.